A study on socio - economic profile and constraints faced by the buffalo milk producers in Guntur district of Andhra Pradesh - A. ANITHA, G. CHANDRA SEKHAR REDDY S. JAGADEESWARA RAO (Indian Journal of Animal Production and Management, 2019)
An investigation was carried out to study the socio – economic profile and constraints faced by thebuffalomilk producers in Guntur district of Andhra Pradesh. It was observed that majority of milk producers belongedto middle age (31- 55 years) group followed by old (above 55 years) and young age (upto 30 years) groupsin small farmers, commercial and landless milk producers. Most of the commercial milk producers andsmall farmers belonged to open category (kamma / kapu / reddy caste )followed by backward caste andscheduled caste. Majority of buffalo milk producers were literate ranging from primary to graduation levelof education. Majority of milk producers in small farmer category had agriculture as main occupation anddairying as subsidiary occupation. Landless milk producers had agriculture labour as main occupation anddairying as subsidiary occupation, whereas, commercial milk producers had dairying as main occupation.Majority of commercial milk producers had more extension contact and mass media exposure as comparedto small farmers and landless milk producers.High cost of pure bred buffaloes, feed ingredients, nonremunerativeprice for milk, feed and fodder shortage and high incidence of repeat breeding in buffaloeswere found to be major constraints felt by the milk producers in the study area. Problem of silent heat,repeat breeding, lack of sufficient knowledge to the farmers about scientific feeding and management andinadequate facilities for diagnostic purpose were observed to be constraints felt by the field veterinariansin Guntur district